KEMATANGAN KARIR PESESRTA DIDIK XI SMK NEGERI 01 BELIMBING HULU KABUPATEN MELAWI TAHUN 2017 - Novitasari Novitasari; Yuline Yuline; Luhur Wicaksono (Universitas Tanjungpura, 2018)
AbstractCareer maturity is the succes of learners to complete the ask of development in accordance with the stages of career development. This study aims to analyze of career maturity student XI of SMK Negeri 01 Belimbing Hulu Kabupaten Melawi Year 2017. The method used is descriptive method and the form of research is survey form. The population in this study as many as 31 students. This research uses quantitative research. Data collection techniques used are direct communication in the form of interviews and indirect communication techniques in the form of questionnaires. Data analysis techniques using the formula percentage. Based on the results of data analysis career maturity service research about readiness to achieve the score in the category of